Characteristics of beef finished on selected feeding regimes - Allen, Dell M.; Hunt, Melvin C.; Kropf, Donald H.; Gutowski, G.; Harrison, A.; Smith, M.E.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station, 2011)
Thirty-eight crossbred steers of known background were randomly assigned to four feeding regimes. All initially were fed on a brome and bluestem pasture supplemented during winter with alfalfa and protein. Ten grass-fed animals were slaughtered directly off pasture at the end of summer. Ten steers were fed an additional 49 days (short-fed), and eight 98 days (long-fed) on 80 percent concentrate and 20 percent corn silage. In addition, ten silage-fed animals were fed 60 percent corn silage and 40 percent concentrate for 98 days. Carcass characteristics were evaluated along with shear force (tenderness) and taste panel responses.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Corn Silage; Carcass characteristics; Tenderness